(untitled) (Journal of Bangladesh Institute of Planners, 2015)
Rural roads are the last link of the transport network that fulfils demand of the product all over the country. Roads have to be maintained from time to time for ensuring serviceability. The study conducted on the Road Maintenance Branch of LGED. The objectives of the study are to investigate current road maintenance practice in LGED through interviews, questionnaires from the LGED staff and other people involved in road projects. It is found that building new roads cost lots of money, but without maintaining the roads properly, they deteriorate very quickly. The problems faced during the road maintenance are selection of road with priorities for maintenance where allocation of funding is very limited. They usually select roads for maintenance based on road IRI (International Roughness Index) value and hierarchy of roads. For example, maintain Upazila roads first which have higher IRI value then union roads. As a result, some village roads which are more important than Upazila roads are not maintained and other Upazila roads not in use for any traffic. According to LGED, per km road maintenance cost is about one third of the total road construction cost. So, it is not logical to allocate fund to those unimportant roads, where important roads are still not maintained. In this regard, four factors (road maintenance cost, road type, and settlement hierarchy and traffic volume) are considered for selection of priority road for maintenance. This may help to proper utilization of money. Settlement hierarchy is determined by centrality score, where fifteen settlements in Phultola Union are ranked based on demographic factors, service, facilities, public utilities, infrastructure and resource information. Road maintenance cost are calculated based on IRI value, where road repairing cost per km based on IRI value known to LGED officials is multiplied by total road length. The data is also analysed using a weight index method to obtain the result. From the result, it is found that 45% village road type A (Pucca) and 35% village road type B (Pucca) are given more weight than Union road. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 209-220